The Influence Of Leadership, Work Climate And Work Motivation On The Performance Of High School Teachers - Hamijoyo, Fransiskus; Wijayanti, Wiwik (UNIVERSITAS PAKUAN, 2025)
This research aims to to find out the influence of leadership, work climate and work motivation on the performance of high school teachers in Malinau Regency. The type of research uses a quantitative research design. The research locations consisted of SMAN 1 Malinau, SMAN 3 Malinau, SMAN 8 Malinau, St. Henricus Leven Catholic High School, Development High School and Darma Bakti High School Malinau. The sampling technique used Isaac and Michael's formula with a margin of error of 5% totaling 130 respondents from the research population of 195 respondents. The instrument used to measure leadership, work climate, work motivation and teacher performance is a questionnaire. The data analysis technique used is multiple regression test. The results of the study showed that: (1) there was a significant influence of leadership on the performance of high school teachers in Malinau Regency, with a significance value of 0.000 0.05, (2) there was no significant influence of work climate on the performance of high school teachers in Malinau Regency, with a significance value of 0.483 0.05, (3) there was a significant influence of work motivation on the performance of high school teachers in Malinau Regency, with a significance value of 0.000 0.05, and (4) there was a significant influence of leadership, work climate, and work motivation on the performance of high school teachers in Malinau Regency, with a significance value of 0.000 0.05.